Writing Skill of Engineering students of Government and Self-financing Colleges: A Comparative Study - Saravanan, J.; Prakash, A.; Selvakumar, R. Saravana (Indonesian Journal of EFL and Linguistics, 2018)
This study compares and analyses the writing performance of engineering students studying in government and Self-financing colleges in Tuticorin district. The subjects of the study comprised of 75 randomly selected first year students from three engineering colleges located in Tuticorin district. The elicitation instrument used for the present study was essay writing and the subjects were asked to write an essay on â€œAdvantages and Disadvantages of using mobile phone.â€ Descriptive method was adopted for collecting data. The errors were identified and classified into ten categorizations like verb tense, subject-verb agreement, prepositions, conditional sentences, singular/plural form, sentence fragment, word order, spelling, capitalization and double negatives. The results showed that the engineering students made seven most common errors in verb tense, subject-verb agreement, prepositions, conditional sentences, singular/plural form, sentence fragment and word order due to lack of understanding, poor acquisition of grammar rules, intra-lingual errors and interference of the learnersâ€™ mother tongue.